A mixed methods systematic review exploring infant feeding experiences and support in women with severe mental illness - Natasha Baker; Debra Bick; Louise Bamber; Claire A. Wilson; Louise M. Howard; Ioannis Bakolis; Tayana Soukup; Yan‐Shing Chang (Wiley, 2023)
Abstract There are many benefits of breastfeeding to women and their infants but meeting the recommended 6 months of exclusive breastfeeding is likely to be more challenging for women with severe mental illness (SMI). This is the first systematic review that aims to examine evidence of (a) infant feeding outcomes in women with SMI and the factors associated with this, (b) the experiences of infant feeding and infant feeding support for women with SMI, (c) interventions for supporting infant feeding among these women and (d) health care professionals' attitudes toward supporting infant feeding in women with SMI. Mixed methods systematic review was carried out using the principles of Joanna Briggs Institute's (JBI) 'convergent integrated' methodology. CINAHL, PsycINFO, Medline and MIDIRS were used to search literature between 1994 and 2022. The quality of selected articles was assessed using JBI critical appraisal tools and thematic synthesis was undertaken to obtain findings. Eighteen papers were included in the final review. Women with SMI were less likely to initiate and continue breastfeeding than women without SMI. Several challenges with breastfeeding were highlighted, and while these were often linked to women's mental health difficulties, inconsistent advice from health care professionals and poor support with breastfeeding further compounded these challenges. This review highlights that policy and practice need to take into account the individual challenges women with SMI face when planning, initiating and maintaining breastfeeding. Education and training for health care professionals are needed to enable them to provide tailored infant feeding support to women with SMI, which reflects their individual needs.